PENGARUH BRAND AWARENESS DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA KARTU GSM PRABAYAR SIMPATI (STUDI KASUS PADA KONSUMEN KECAMATAN PEDURUNGAN) - Amalia, Aida Zahrotu; Waluyo, Handoyo Djoko; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
This research was motivated by the phenomenon of the mobilephone technology’s development which makes the growth of the cellular network companies, where the competition between mobile networks increasingly stringent. SimPATI Prepaid GSM Card is a prepaid card from PT. Telkomsel which is very well known and always strives to provide the best quality in order to meet the needs and expectations of its customers. SimPATI proves that customer satisfied with the products by obtaining the first rank in the ICSA index, but from 2010 to 2012 the percentage continues to decline. In addition, simPATI is a top brand in relation to GSM prepaid card products, but the percentage of top brand index from 2010 to 2012 continued to decline.The objective of this research is to examine the influence of brand awareness and product quality on customer loyalty through customer satisfaction with simPATI GSM Prepaid Card. The type of this research is explanatory research, with technique of collecting data through questionnaires, interviews and a literature study. The technique of sampling using multistage area sampling and purposive sampling. The sample in this research were 100 respondents who are the users of simPATI GSM Prepaid Card in Pedurungan District. This research uses qualitative and quantitative analysis techniques. Quantitative analysis uses validity test, reliability test, correlation coefficient, simple and multiple regeression analysis, the coefficient of determination, a significant test (t and F) and path analysis using SPSS for windows version 20.0.The results of this research approved that brand awareness (X1), and product quality (X2) partially or simultaneously can influenced customer satisfaction (Z) and customer loyalty(Y). According the result of path analysis, the influence of brand awareness and product quality toward customer loyalty will be greater if through customer satisfaction.Based on the research results, the researcher suggests that the company has to improve the provision’s information on the products’s diversity, provide new innovations on features / facilities, and allows users to use the features / facilities so that the products can improve customer satisfaction to create customer loyalty on the simPATI GSM Prepaid Card.